2015
DOI: 10.1186/s12917-015-0322-z
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and molecular characteristics of hepatitis E virus in household-raised pig population in the Philippines

Abstract: BackgroundHepatitis E virus (HEV) infection is a significant public health concern in Asia, and swine is an important source of sporadic HEV infection in human. However, no epidemiological data are available regarding HEV infection among the swine or human population in the Philippines. To assess the HEV infection status among pigs in rural areas, we investigated the molecular characteristics and seroprevalence of HEV among household-raised pigs in San Jose, Tarlac Province, the Philippines.ResultSerum and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 46 publications
12
31
0
1
Order By: Relevance
“…Results of this study showing an overall seroprevalence of 65.0% in pigs were consistent with previous findings in mixed age group swine populations reported from western India and China where the anti‐HEV IgG seropositivity was 54% and 50.3%, respectively (Arankalle et al., ; Liu et al., ), although a high seropositivity of 96.50% was reported from adult pigs in Lucknow, India (Shukla et al., ). Several other studies have reported the seropositivity for anti‐HEV IgG in pigs in the range of 6.1%–7.2% from Belgium, 31.0% to 65.0% from France, 49.8% from Germany, 68.0% from the Netherlands and 87.0% from northern Italy (Kim et al., ; Van Hoecke et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…Results of this study showing an overall seroprevalence of 65.0% in pigs were consistent with previous findings in mixed age group swine populations reported from western India and China where the anti‐HEV IgG seropositivity was 54% and 50.3%, respectively (Arankalle et al., ; Liu et al., ), although a high seropositivity of 96.50% was reported from adult pigs in Lucknow, India (Shukla et al., ). Several other studies have reported the seropositivity for anti‐HEV IgG in pigs in the range of 6.1%–7.2% from Belgium, 31.0% to 65.0% from France, 49.8% from Germany, 68.0% from the Netherlands and 87.0% from northern Italy (Kim et al., ; Van Hoecke et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, this study was aimed to determine the prevalence and correlates of HEV infection in the In an international context, the overall seroprevalence of HEV infection found in pigs in Durango is higher than the 9.9% and 29% seroprevalences found in farm pigs in Thailand 10 and Scotland, 11 respectively. The seroprevalence found in our study is comparable with intermedium (46.9-66.4%) seroprevalences in pigs reported in Germany, 12 Italy, 13 Philippines, 14 Switzerland, 15 and China. 16 In contrast, the seroprevalence found in our studied pigs is lower than those (71.2-90%) reported in pigs in Madagascar, 6 Netherlands, 17 Belgium, 18 France, 19 Burkina Faso, 20 and Norway.…”
Section: Discussionsupporting
confidence: 88%
“…For instance, a relatively low (9.9‐29%) seroprevalence of HEV infection in pigs has been reported in Thailand and Scotland . Whereas, intermedium (46.9‐66.4%) seroprevalences of HEV infection have been reported in pigs in Germany, Italy, Philippines, Switzerland, and China . In contrast, high (71.2‐90%) seroprevalences of HEV infection have been found in pigs in Madagascar, Netherlands, Belgium, France, Burkina Faso, and Norway …”
Section: Introductionmentioning
confidence: 99%
“…Globally, HEV-3a appears to be a well-travelled lineage, with sequences found in farmed pigs in Canada, China, Columbia, France, Indonesia, Japan, South Korea, and Philippines. [28][29][30][31][32][33][34][35] It was also recently identified in German wild boars 36 and was the causative agent of an autochthonous human infection in Europe. 37 It should be noted that nonporcine transmission modes are possible and cannot be ruled out completely.…”
Section: Discussionmentioning
confidence: 99%
“…All of the National University Hospital (NUH, Singapore) sequences in this study fall within subtype 3a on the phylogenetic tree. Globally, HEV‐3a appears to be a well‐travelled lineage, with sequences found in farmed pigs in Canada, China, Columbia, France, Indonesia, Japan, South Korea, and Philippines . It was also recently identified in German wild boars and was the causative agent of an autochthonous human infection in Europe .…”
Section: Discussionmentioning
confidence: 99%